2015
DOI: 10.1038/tp.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Longevity factor klotho and chronic psychological stress

Abstract: Chronic psychological stress is associated with accelerated aging and premature morbidity and mortality; however, the biology linking chronic psychological stress and its maladaptive effects remains largely unknown. Klotho is a pleiotropic hormone that regulates the aging process and promotes better brain and body health. Whether klotho is linked to psychosocial stress or its negative impact in humans has not been investigated. To address this gap, we recruited 178 healthy women who were either chronically hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 53 publications
2
60
1
2
Order By: Relevance
“…It has been suggested that this KL variant may influence the trafficking and the catalytic activity of Klotho protein [46], giving a survival advantage to KL-VS heterozygotes [46,60], who have also higher serum Klotho levels [46,61] and better cognitive functions [61,62]. Very recently, lower levels of Klotho have been associated with high chronic stress and with depressive symptoms in young, otherwise healthy women [63], suggesting that Klotho may serve as a novel biological link connecting stress, depression, and risk for accelerated disease development. Therefore, some KL genetic variants, including KL rs9536314, may modulate serum Klotho levels and lower levels of circulating Klotho were further linked to high chronic stress and depressive symptoms partly explaining the possible role of KL locus in the response to antidepressant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this KL variant may influence the trafficking and the catalytic activity of Klotho protein [46], giving a survival advantage to KL-VS heterozygotes [46,60], who have also higher serum Klotho levels [46,61] and better cognitive functions [61,62]. Very recently, lower levels of Klotho have been associated with high chronic stress and with depressive symptoms in young, otherwise healthy women [63], suggesting that Klotho may serve as a novel biological link connecting stress, depression, and risk for accelerated disease development. Therefore, some KL genetic variants, including KL rs9536314, may modulate serum Klotho levels and lower levels of circulating Klotho were further linked to high chronic stress and depressive symptoms partly explaining the possible role of KL locus in the response to antidepressant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in spite of available evidences on the mechanisms regulating aging and stress responses (Koolhaas et al., 2011; McEwen, 2007; Prather et al., 2015) and the profound effect of stress on pathophysiology (Bartolomucci, 2007; McEwen, 2007), this association is not mechanistically understood nor has its causation been explored in animal models thus far.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it is not unreasonable to speculate that levels of α-Klotho in CSF may be inversely correlated with physiological stress, and that decreased CSF α-Klotho may be involved in raising the blood pressure of stressed individuals. This connection between stress and reduced α-Klotho is strengthened by the observation that women with chronic psychological stress caused by raising a child on the autistic spectrum have lower levels of α-Klotho in serum than women raising a non-autistic child (Prather et al, 2015). Thus, it is quite plausible that stress decreases α-Klotho expression at multiple locations, and is therefore central to the effects of elevated stress on aging.…”
Section: What Is the Target Of Choroid Plexus / Csf α-Klotho?mentioning
confidence: 99%